Trichoderma Species Biosorption Of Nickel And Cadmium From Aqueous Solutions - Low, Pui Man (2017)
The effect of ph on growth of trichoderma sp. In shake flask culture was studied. The highest biomass was obtained at ph 5 which is 1.45g in 100 ml of liquid media. In this research, the biosorbent was characterized by fourier transform infrared spectroscopy (ftir) and scanning electron microscope (sem), energy dispersive x-ray spectroscopy (edx) and ph point of zero charge (phpzc). The optimum biosorption conditions were determined as a function of ph, biosorbent dosage, and contact time. The equilibrium data were better fit by the langmuir isotherm model than by the freundlich isotherm. The maximum adsorption capacity of nickel and cadmium were found to be 5.456 mg/g and 2.380 mg/g respectively. The central composite design (ccd) in response surface methodology was used for designing the experiments as well as for full response surface estimation. The optimum condition for maximum removal of nickel and cadmium from an aqueous solution of 50 mg/l were as follows: ph 4.92, biosorbent dosage (0.70 g), contact time (8.28 hours) for nickel and ph 9.99, biosorbent dosage (0.60 g), contact time (11.93 hours) for cadmium. The high correlation coefficient (/?2 = 0.877 for nickel, r2 = 0.959 for cadmium) between the models and experiment data showed that the models were able to predict the removal of nickel and cadmium from aqueous solution by using trichoderma sp. Efficiently.